Optimization of femtosecond laser cutting of biodegradable polymer for medical devices manufacturing - Stępak, Bogusz; Antończak, Arkadiusz J.; Abramski, Krzysztof M. (Photonics Letters of Poland, 2016)
This paper describes the experimental parameters involved in the femtosecond laser micromachining of biodegradable poly(L-lactide) which is frequently used in biomedical applications such as vascular stents or scaffolds. We investigated the influence of laser pulse energy, scanning strategy and number of overscans on the laser cutting throughput. The process parameters that enable reducing of a heat affected zone were determined. As a result, the optimal scanning strategy was determined in order to obtain high aspect ratio trenches in 380 ?m thick biodegradable polymer sheet. Full Text: PDF References W. Jia et al. "Effects of high-repetition-rate femtosecond laser micromachining on the physical and chemical properties of polylactide (PLA)", Opt. Express 23, 21 (2015). CrossRef F. Hendricks, R. Patel, and V.V. Matylistsky, "Micromachining of bio-absorbable stents with ultra-short pulse lasers", Proc. SPIE 9355, 935502 (2015). CrossRef W.Y. Yeong et al. "Annealing of Biodegradable Polymer Induced by Femtosecond Laser Micromachining", Adv. Eng. Mater. 4, 12 (2010). CrossRef K. Stolberg et al. "IR and green femtosecond laser machining of heat sensitive materials for medical devices at micrometer scale", Proc. SPIE 8968, 89680E (2014). CrossRef F. Hendricks et al. "High aspect ratio microstructuring of transparent dielectrics using femtosecond laser pulses: method for optimization of the machining throughput", Appl. Phys. A 117, 1 (2014). CrossRef A. Antończak et al. "Degradation of poly(l-lactide) under CO2 laser treatment above the ablation threshold", Polym. Deg. Stab. 109, 97-105 (2014) CrossRef B. Stępak et al. "The influence of ArF excimer laser micromachining on physicochemical properties of bioresorbable poly(L-lactide)", Proc SPIE 9736, 97361T (2016). CrossRef